An Analysis on English Education Students’ Grammatical Error in Writing Essay - Meliana Muliawati; Restu Arini (Jurnal Dunia Pendidikan, 2023)
This study discusses the grammatical error analysis performed on essay writing. Errors have become commonplace for foreign language learners. The impact of an error in writing can make the sentence not meet the proper language rules, and will cause the sentence to be difficult to understand or even its meaning not conveyed properly. The main objective of this study is to find the types of errors based on the surface strategy taxonomy in essays written by 26 senior college students. The methodology used in this study is descriptive qualitative and begins with the stage of collecting essays written by students, followed by analyzing student essays to find errors by reading them slowly, then classifying the errors based on surface strategy taxonomy. The result shows there are 86 errors found in the students essay: 45 errors in the omission category, 12 errors in the addition category, and 20 errors in the miss formation type, and 9 errors in misordering category. Of the student essays that have been analyzed, this study implies that the students' writing skills are moderately good; however, there are some aspects of trivial errors that were made by students. Thus, an appropriate strategy for mastering grammar and writing should be the concern of the college, but it is also unfortunate because there are some aspects of trivial errors but there are still students who make errors.